Democracy and democratization : processes and prospects in a changing world - Sørensen, Georg, 1948- (Dilemmas in world politics., 2008)
"What is democracy? What are the pitfalls and the positive potentials in the growing trend toward democratization? This book examines the prospects for democracy in the world today and frames the central dilemma confronting all states touched by the process of democratization. Georg Sørensen clarifies the concept of democracy, shows its application in different contexts, and questions whether democratic advancement will continue -- and if so, at what price. The consequences of democracy for economic development, human rights, and peaceful relations among countries are illuminated in both their positive and negative aspects. This third edition includes an entirely new chapter on the promotion of democracy from the outside and current issues of state building in Iraq. Further revisions include updates to the section on the prospects of democracy in today's world, an extended discussion of the economic performance of recently democratized countries, and an evaluation of the possibilities for further democratic consolidation. There are also new case studies, examples, and anecdotes to illustrate historical as well as contemporary instances of democratic transition. Democracy, as Sørensen convincingly portrays it, is a value in itself as well as a potential promoter of peace, prosperity, and human well-being. But democracy is not inevitable, and actions at every level -- from the individual to the international -- are necessary to ensure that frail or 'frozen' democracies do not flounder and that established democracies flourish."--Publisher description